Quarterback draw eaudiobook - Burton, Jaci (Play By Play, 2015)
Grant Cassidy knows how to be a football star—flash that dazzling smile, throw the winning pass, get the girl. But while the hot quarterback loves the game and the lifestyle, no woman has come close to catching his heart. Then he matches wits with a smart, gorgeous model, and Grant finds himself wanting more than a fling. Supermodel Katrina Koslova might live in a world of glitz and camera flashes, but she works hard to provide for the family that relies on her. She doesn't have time for fun—much less a boyfriend—but Grant seems determined to be the exception to Katrina's rule. Their explosive chemistry is undeniable, but Katrina is afraid to let go and rely on anyone but herself. Grant intends to ease her fears and prove he's a man of style and substance—a man she can count on. Contains mature themes.